IL-18 PROMOTER POLYMORPHISM AND IL-18 SERUM LEVELS IN ASSOCIATION WITH RELAPSING-REMITTING MULTIPLE SCLEROSIS - Boncho Grigorov; Anastasiya Trenova; Antonia Grigorova; Spaska Stanilova (Peytchinski Publishing, 2020)
Purpose: Multiple sclerosis is the immune-mediated disorder whose etiology is not completely understood. The present study aimed to survey association between the promoter polymorphism IL18 -607C/A (rs1946518), the serum concentration of IL-18 and susceptibility to relapsing-remitting multiple sclerosis (RRMS) in Bulgarian patients Material and Methods: This case-control study includes 159 RRMS patients with disease-modifying therapy (DMT) and 162 age-sex-matched healthy volunteers. All included subjects were genotyped by ARMS-PCR while serum levels were measured by enzyme-linked immunosorbent assay (ELISA). Results: Our results revealed significant differences in the serum levels of IL-18 according to the gender, the onset of disease and the type of disease-modifying therapy. The serum levels of IL-18 are significantly higher in RRMS men compared to RRMS women and the RRMS men with late-onset of the disease (above 30 years) also demonstrated significantly increased serum levels than the women with late-onset of disease and even with healthy men. The RRMS patients treated with interferon-beta showed significantly increased IL-18 serum level than those treated with glatiramer acetate. Conclusions: Our study shows that the promoter polymorphism IL18 -607C/A is not associated with susceptibility to RRMS in Bulgarian patients as well as the serum level of the cytokine. The observed differences in the serum level of IL-18 in RRMS patients according to gender and the response to therapy could be used as a biomarker to the course of the disease.